The Zone of the Silent Film. From Archeology of Cinema to the Digital Utopia - Gilić, Nikica (2011)
Digital era gives new perspective on the past, present and the future of the silent film. Based on the experience of Silent film festival held annually in Zagreb, it is possible to theorize about the nature of silent film in its various forms and functions. Basically, because the invention of sound film there was no concept of silent film, so it seems interesting to think about the media in the digital era from this perspective.